PENGARUH TINGKAT SUKU BUNGA, INFLASI, DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PADA BANK KONVENSIONAL (STUDI KOMPARASI PADA BANK CENTRAL ASIA DAN BANK MANDIRI) - Natari, Sheila Try (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study focuses on the role of macroeconomic variables and ownership structure on financial performance (ROA) at Bank Mandiri and Bank BCA. The macroeconomic variable was measured by the interest rate of Bank Indonesia and inflation, while the variable of ownership structure was measured by managerial ownership and institutional ownership. This research was conducted using Multiple Regression Analysis method. The result of this study indicates that macroeconomic variables are more influential on the financial performance compared with the variable of ownership structure from both of the banking firms. The above-mentioned macroeconomic variable is inflation. Inflation affects ROA because along with the rising of the national inflation rate, the interest rate will rise as well to reduce the circulation of money supply in the society. That results to a higher public inclination to invest their money in the bank. The increasing amount of third party deposits in the bank will raise the asset of the firm. The assets are used by the firm to increase profits which results to the increase of return value of the firm's total assets. In the end, the assessment of the firm's performance is better because the ROA shows improvement.Keywords: macroeconomic variables, ownership structure, financial performance, interest rate, inflation, managerial ownership, institutional ownership, ROA, multiple regression.